Diagnostic Routes and Time Intervals for Ovarian Cancer in Nine International Jurisdictions; Findings From the International Cancer Benchmarking Partnership (ICBP). Issue 12 (December 2022) - Menon, Usha; Weller, David; Falborg, Alina Zalounina; Jensen, Henry; Butler, John; Barisic, Andriana; Knudsen, Anne Kari; Bergin, Rebecca J.; Brewster, David H.; Cairnduff, Victoria; Fourkala, Evangelia Ourania; Gavin, Anna T.; et al.
Abstract : (Abstracted from Br J Cancer 2022;127:844–854) Ovarian cancer (OC) is the gynecological malignancy with the highest mortality, partially attributable to the lack of effective screening for early-stage disease. Despite inadequate screening methods, there exists significant international variation in the proportion diagnosed at late stage and in OC survival across all stages.